Perceptions of Healthcare Providers about Pharmacists' Clinical Roles in Patient Care in Ghana - Akua A. Appiah-Num Safo; Olihe N. Okoro; Joseph Attakorah (University of Minnesota Libraries Publishing, 2022)
Background: Clinical pharmacy practice is distinguishable from the dispensing model by its focus on direct patient care. To function effectively in this role, pharmacists need to have clinical competencies, hence the establishment of the Doctor of Pharmacy (PharmD) program. In Ghana, the PharmD program is in its early stages; graduating its first set of pharmacists in 2018. There is therefore need to understand how these recent PharmD graduates are engaging in clinical roles and the perceptions of other health professionals they need to work collaboratively with. Methods: Four different focus group discussions (FGDs) were conducted with physicians, nurses and pharmacists in separate sessions. Questions explored perceptions of the clinical roles of pharmacists. The FGDs were audio-recorded and transcribed verbatim. A thematic analysis of the transcripts was conducted. Results: Perceptions around the roles of clinical pharmacists were in two categories - (1.) Roles associated with the provision of direct patient care [(i.) assurance of appropriateness, and (ii.) optimization of pharmacotherapy; and (2.) Roles involving participation in inter-professional collaborative care with other healthcare professionals through their (i.) contribution of pharmacotherapy expertise, and (ii.) input in interprofessional education and practice. Conclusion: Findings from the study highlight perceived contributions of pharmacists, and potential for more relevance to clinical care, while also drawing attention to the emergence of clinical roles of pharmacists in healthcare systems in a global context. There is continuing need for advocacy for the pharmacy profession and policy changes in healthcare delivery models to maximize potential benefits of clinical pharmacists to health outcomes.